Folk Genres in the Collection "A Thousand and One Songs," Compiled by Manuk Abeghyan and Komitas - Dolukhanyan, Aelita (Bulletin of Yerevan University B: Philology, 2026)
Manuk Abeghyan continued the important work begun by the great educator Khachatur Abovyan during his collaboration with the brilliant Komitas at the Gevorkian Seminary, which greatly contributed to the transmission of folk songs to future generations.• Abeghyan was an outstanding folklorist: he was perfectly familiar with significant works of world folklore and skillfully selected the materials that should be recorded and the precise lexical variant in which they should be transmitted to succeeding generations. Thus, Abeghyan promoted the continuity of folk artistic thought, a cause to which were devoted not only the immensely valuable publications of the originals but also the theoretical and scientific justifications.    The songbook "A Thousand and One Songs," compiled by M. Abeghyan and Komitas, is one of the monuments of Armenian culture, possessing enduring value.
Keywords: M. Abeghyan; Komitas; folk songbook; epic song; love songs; traveler's songs; peasant